Penerapan Pendekatan TaRL Berbantuan Media Kahoot pada Materi Teks Anekdot di SMA Kota Semarang - Kamarullah, Heike; Wismanto, Agus; Rahayu, Winarni (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of this study is to explore the application of the Teaching at the Right Level (TaRL) approach supported by Kahoot media on anecdotal text material in Semarang city high schools, especially at SMA Negeri 5 Semarang. Students have differences in abilities, both in terms of level of understanding, learning style, and background. The TaRL approach considers these differences and ensures that learning matches each learner's ability level. The use of learning media is also an important element in the application of this approach. One of them is the use of Kahoot media. The use of Kahoot can also assist teachers in taking diagnostic assessments. This research method uses qualitative with a type of qualitative descriptive research. The sample in this study was one class in class X-10 with a total of 36 learners from the entire population selected using the Purposive Sampling technique. The data collection technique used by researchers in this study is the learning results of students obtained from interviews and observation techniques by observers. Data analysis techniques use descriptive qualitative. The validity used in this research is triangulation of sources. The results of data analysis and discussion can be concluded that the application of the TaRL approach assisted by Kahoot media on anecdotal text material shows significant potential in learning effectiveness.